The 65% Instructional Expenditure Ratio and Student Achievement: Does Money Matter? - Timothy B Jones; John R Slate (Arizona State University, 2010)
In this study, the researchers examined the extent to which Texas public school districtsâ compliance with the 65% instructional expenditures ratio was related to student academic success on the Texas Assessment of Knowledge & Skills tests. Separated into three groups (i.e., 65% instructional expenditures and higher, 60 to 65% instructional expenditures, and less than 60% instructional expenditures), statistically significant differences were yielded among these groups in the TAKS Reading, Math, Social Studies, Science, and Writing measures. School districts that spent less than 60% of their monies on instructional expenditures had the lowest percent passing rates in all five TAKS tests. Effect sizes ranged from small to large and were consistent across ethnic groups. Implications of these findings and suggestions for further research are discussed.